Promoting Education for Sustainable Development: Roles of Teacher - Bakhati, Pramila (Journal of Training and Development, 2015)
Human beings are considered as the most intellectual living beings in this Universe because they are able to cope with all the natural resources for their personal needs and preserving the things as well. Due to the growing population and immense using of resources, the things which we get from the nature are being destroyed by using in improper way. Our common home: the Earth is now in crisis as a result of limited awareness, egotism and understanding about the real values of nature and natural resources. In this problematic situation, Sustainable Development (SD) is emerged as a window of hope and later Education for Sustainable Developed (ESD) is appeared to promote the SD. However, if the knowledge is not transformed into behavior and practical life, the knowledge will be nothing or the meaningless. DOI: http://dx.doi.org/10.3126/jtd.v1i0.13086 Journal of Training and Development Vol.1 2015: 21-26